AN ANALYSIS OF THEMATIC PROGRESSION IN THE BACKGROUND SECTION OF ENGLISH DEPARTMENT UNDERGRADUATE STUDENTS’ THESIS OF BENGKULU UNIVERSITY IN PERIOD 2017 - Nanik Anjar Yani; Bambang Suwarno; Gita Mutiara Hati (Journal of English Education and Teaching, 2018)
The aim of this research was to find out the types and the dominant type of thematic progression in the background section of theses written by undergraduate students of the English Department of Bengkulu University (UNIB) in 2017. The design was descriptive quantitative. The sample consisted of 16 background sections of undergraduate theses, which were chosen randomly. The data were collected by the documentation instrument. The result showed that there were three types of thematic progression, namely, constant theme, linear theme, and split rheme. Furthermore, the linear theme was the dominant type.The order of frequency was as follows: linear theme (50.07%), constant theme (45.81%), and split rheme (4.10%). The conclusion was that all types of thematic progression were used and that the linear theme was the most common in the background section of the UNIB undergaduate theses.